Bedaquiline: An Insight Into its Clinical Use in Multidrug-Resistant Pulmonary Tuberculosis - Ahmad, Asad; Akhtar, Juber; Ahmad, Mohammad; Khan, Mohammad Irfan; Wasim, Rufaida; Islam, Anas; Singh, Aditya (Drug Research, 2024)
Every year, the World Health Organization reports 500,000 new cases of drug-resistant tuberculosis (TB), which poses a serious global danger. The increased number of XDR-TB and MDR-TB cases reported worldwide necessitates the use of new therapeutic approaches. The main issues with the antitubercular medications now in use for the treatment of multidrug-resistant tuberculosis are their poor side effect profile, reduced efficacy, and antimicrobial resistance. One possible remedy for these problems is bedaquiline. The need for better treatment strategies is highlighted by the strong minimum inhibitory concentrations that bedaquiline (BDQ), a novel anti-TB medicine, exhibits against both drug-resistant and drug-susceptible TB. Bedaquiline may be able to help with these problems. Bedaquiline is a medication that is first in its class and has a distinct and particular mode of action. Bedaquiline is an ATP synthase inhibitor that is specifically directed against Mycobacterium tuberculosis and some nontuberculous mycobacteria. It is metabolized by CYP3A4. Bedaquiline preclinical investigations revealed intralesional drug biodistribution. The precise intralesional and multi-compartment pharmacokinetics of bedaquiline were obtained using PET bioimaging and high-resolution autoradiography investigations. Reduced CFU counts were observed in another investigation after a 12-week course of therapy. Meta-analyses and systematic reviews of phase II trials on bedaquilineʼs efficacy in treating drug-resistant tuberculosis in patients reported higher rates of cure, better culture conversion, and lower death rates when taken in conjunction with a background regimen. Here is a thorough medication profile for bedaquiline to aid medical professionals in treating individuals with tuberculosis.
Keywords: bedaquiline; mycobacterium tuberculosis; multidrug resistance; tuberculosis